1997
DOI: 10.1007/s004210050164
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and performance adaptations to interval training in endurance-trained cyclists

Abstract: This study examined the effects of sustained high-intensity interval training (HIT) on the athletic performances and fuel utilisation of eight male endurance-trained cyclists. Before HIT, each subject undertook three baseline peak power output Wpeak tests and two simulated 40-km time-trial cycling performance (TT40) tests, of which the variabilities were 1.5 (1.3)% and 1.0 (0.5)%, respectively [mean (SD)]. Over 6 weeks, the cyclists then replaced 15 (2)% of their 300 (66) km.week-1 endurance training with 12 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
79
2
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 24 publications
17
79
2
13
Order By: Relevance
“…Improvements in aerobic and anaerobic capacity have been noted in previous studies that predominantly used high-intensity training (Bayati, et al, 2011;Lindsay, et al, 1996;Westgarth-Taylor, et al, 1997;Tabata, et al, 1996;Tabata, et al, 1997;Hottenrott, et al, 2010;Acevedo & Godfarb, 1989;Garber, et al, 2011;Midgley, et al, 2006). These studies have noted an improvement in aerobic capacity, anaerobic capacity, peak power output, peak sustained power, maximum blood lactate levels, and time to fatigue.…”
Section: Chapter 4 Resultsmentioning
confidence: 71%
“…Improvements in aerobic and anaerobic capacity have been noted in previous studies that predominantly used high-intensity training (Bayati, et al, 2011;Lindsay, et al, 1996;Westgarth-Taylor, et al, 1997;Tabata, et al, 1996;Tabata, et al, 1997;Hottenrott, et al, 2010;Acevedo & Godfarb, 1989;Garber, et al, 2011;Midgley, et al, 2006). These studies have noted an improvement in aerobic capacity, anaerobic capacity, peak power output, peak sustained power, maximum blood lactate levels, and time to fatigue.…”
Section: Chapter 4 Resultsmentioning
confidence: 71%
“…Previous studies of the effect of short-term (~3 wk) intensified training have reported improvements in athletic performance [4,5,8,10], accompanied by shifts in substrate metabolism (from carbohydrate to fat). There have been mixed responses of enzyme activity after intensified training [1,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism that has been proposed to explain improvements in endurance performance of athletes is a change in neuromuscular recruitment patterns [5,12]. But there appears to be little known about the neuromuscular response to HIT and hence it is not possible to understand its role in enhancing performance in response to HIT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the importance of V O2max as a valid measure for assessing performance improvements after HIIT remains in question, due to findings reporting only a modest association between V O2max improvements and performance improvements [36] and since numerous HIIT studies involving well-trained endurance athletes did not even report changes in V O2max after training [32,33,37,38] .…”
Section: O2max and Exercise Training In Trained Athletesmentioning
confidence: 99%
“…In endurance-trained athletes, small improvements in performance are critical to success; therefore, establishing the sensitivity of laboratory-derived variables such as peak power output and LT2 to detect these performance changes is important. High-intensity interval training (HIIT), defined as repeated short-to-long bouts of rather high-intensity (80-100% peak heart rate [26] ) exercise interspersed with recovery periods [27] , has been shown to improve running (3-10 km) [28][29][30] , treadmill roller skiing (12 km) [31] and cycling (15-40 km) [32][33][34][35][36][37][38][39][40] time trial performances in trained athletes, although the majority of these studies involved men only [28,30,[32][33][34][35][36][37][38][39][40] , with only one study combining men and women [31] and another not stating the sex of participants [29] . In response to HIIT, LT2 adaptations in endurance-trained athletes have only been reported in response to training interventions over one year [40] , five months [41] , and in one short-term study where seven HIIT sessions were completed in seven days [39] .…”
mentioning
confidence: 99%